THE ROLE OF MASS MEDIA IN PREVENTING CORRUPTION (Law, State and Telecommunications Review, 2021)
Purpose – The article focuses on the freedom of speech as a basic principle in the activities of mass media against corruption. The attribute of every democratic and law-governed state is freedom of speech, that is, the ability to express their thoughts and beliefs freely. Ukraine is not an exception, for the right of freedom of thought and speech and free expression of ones’ views and beliefs are guaranteed. The existence of an effective media system is the basis for implementing the principle of publicity in the activities of public administration and ensuring effective transparent oversight of its activities. Moreover, mass media play an important role in the political life of the country.Methodology/Approach/Design – The research is based on the methods of systemic and critical analysis.Findings – The ability of domestic journalists to be active participants in anti-corruption reforms is confirmed by many journalistic corruption investigations and high-profile disclosures, which led to the opening of criminal proceedings.